Seven kings - Fultz, John R. (New York : Orbit, 2013)
In the jungles of Khyrei, an escaped slave seeks vengeance and finds the key to a savage revolution. In the drought-stricken Stormlands, the Twin Kings argue the destiny of their kingdom: one walks the path of knowledge, the other treads the road to war. Beyond the haunted mountains King Vireon confronts a plague of demons bent on destroying his family. With intrigue, sorcery, and war, Seven Kings continues the towering fantasy epic that began with Seven Princes.
Includes an excerpt of "Seven sorcerers" by John R. Fultz.
Keywords: Kings and rulers -- Fiction; Magic -- Fiction; Good and evil -- Fiction; Demonology -- Fiction